Spatial analysis of environmental policy stringency effect on the environmental performance of European countries: mitigation options through green growth and green technological innovation - Maria Shabir; Asif Javed; Snober Fazal; Nimra Usman (Environment, Development and Sustainability, 2026)
Against a backdrop of worsening environmental problems, sustainable development and the conservation and protection of nature have become focal points of current debate. Because burning fossil fuels jeopardizes global sustainability, transitioning to green energy worldwide is recognized as a primary strategy to address climate change. Prior work has concentrated on the temporal dynamics of environmental deterioration. This study, by contrast, examines the drivers of ecological footprint (EFP) from a spatio-temporal perspective, focusing on the extent to which green growth (GG), green technological innovation (GTI), and environmental policies (EPS) influence ecological sustainability across 27 European Union (EU) member states over the 1996 to 2020 period. The results of the Wald and likelihood ratio tests confirm that the spatial autoregressive (SAR) model is most suitable for the analysis. The empirical findings indicate that GG, GTI, and EPS in a given country reduce EFP both domestically and in neighbouring countries. Moreover, we examine regional heterogeneity by splitting the sample into Eastern and Western European groups. The empirical findings of heterogeneity analysis reveal that GG exacerbates EFP in Eastern Europe but mitigates it in Western Europe. Policymakers need to take tangible steps to limit environmental harm, incentivize renewable energy, and diversify energy sources. These findings suggest that cross-border cooperation is essential for the sample economies to promote GG and GTI, implement sustainable growth strategies, and improve production efficiency, thereby supporting better environmental outcomes.

Correction: Pollen morphology of cucurbitaceae using microscopic techniques for accurate taxa identification - Haleema Sadia; Khafsa Malik; Rahmatullah Qureshi; Khalid Mehmood; Khushdil Khan; Ahmad Hassan; Shabir Ahmad; Hussain Shah; Huma Gul; Jawaher Alkahtani; Bandar Mohsen Almunqedhi; Rashid Iqbal; et al. (Genetic Resources and Crop Evolution, 2025)

Sustainable biodiesel production from non-food biomass of Cucumis prophetarum via waste peel-based phyto-nanocomposite in membrane reactor: An innovative outlay for waste management and circular bioeconomy - Maria Ameen; Mushtaq Ahmad; Muhammad Zafar; Balal Yousaf; Muhammad Faisal Amin; Iftikhar Ahmed; Shabir Ahmad (Biomass and Bioenergy, 2025)

Variation in Ectotherm Thermal Tolerances With Elevation and Temperature Across Biological Scales - Imran Khaliq; Edward Lavender; Haseeb Kamran; Muhammad Junaid Shahid; Muhammad Sheraz; Muhammad Awais; Mehtab Shabir; Muhammad Yasir; Abdul Hameed; Muhammad Asgher; Abdul Rehman; Maria Riaz; et al. (Global Ecology and Biogeography, 2025)
Aim Variation in thermal tolerances along environmental gradients is assumed to follow similar patterns across different biological scales, including within and between species, and across communities. However, this assumption has yet to be tested using comprehensive datasets collected through standardised methodologies. Location Southern Asia. Time Period 2017–2019. Major Taxa Studied Ants, beetles, grasshoppers, and spiders. Methods We quantified the associations between thermal tolerance traits and elevation or temperature at three biological scales (community, broad taxonomic group, and species) along two distinct elevational transects in Southern Asia. In total, we measured thermal tolerances of over 15,000 individuals from 114 arthropod species belonging to four invertebrate taxa (ants, beetles, grasshoppers, and spiders). We compared the relationships at each scale using mixed‐effects models. Results At the community scale, across all individuals of all species, we found a consistent decline in the values of three thermal tolerance traits (upper tolerance, lower tolerance, and tolerance breadth) with elevation along the Himalayan transect but an increase in the values of upper and lower tolerance along the Sulaiman transect. The relationships of thermal tolerance traits and elevation/temperature varied among the groups and species between the Himalayan and Sulaiman transects. This suggests that factors beyond elevation, including vegetation composition, microclimate, landscape features, and local adaptation, drive observed variation in thermal tolerance traits among and within species. Conclusion Our study highlights the interplay between thermal physiology and the environment across different habitats and biological scales. Our findings indicate that predicting biodiversity responses to environmental change based on thermal tolerance–environment relationships requires careful consideration of group‐ and species‐level variation. This is essential for improving the accuracy of climate change impact assessments on biodiversity.

Pollen morphology of cucurbitaceae using microscopic techniques for accurate taxa identification - Haleema Sadia; Khafsa Malik; Rahmatullah Qureshi; Khalid Mehmood; Khushdil Khan; Ahmad Hassan; Shabir Ahmad; Hussain Shah; Huma Gul; Jawaher Alkahtani; Bandar Mohsen Almunqedhi; Rashid Iqbal; et al. (Genetic Resources and Crop Evolution, 2025)

Investigating a new energy justice index on carbon emissions: A global study of 95 economies during 1996–2021 - Maria Shabir; Caterina De Lucia; Pasquale Pazienza (Journal of Environmental Management, 2025)

Environmental cost of natural resources, globalization, and economic policy uncertainty in the G-7 bloc: do human capital and renewable energy matter? - Awais Dastgeer; Maria Shabir; Muhammad Usman; Mustafa Kamal; Mohammad Faisal Khan (Environmental Science and Pollution Research, 2023)

Analyzing asymmetric ecological performance under structural change, technological innovation, and trade diversification: fresh insights from the USA - Md Minhazul Islam; Paiman Ahmad; Maria Shabir; Muhammad Usman; Mustafa Kamal (Environmental Science and Pollution Research, 2023)

Pesticide residues in fruits and vegetables from Pakistan: a review of the occurrence and associated human health risks - Jabir Hussain Syed; Ambreen Alamdar; Ashiq Mohammad; Karam Ahad; Zunera Shabir; Haroon Ahmed; Syeda Maria Ali; Syed Gul Abbas Shah Sani; Habib Bokhari; Kevin D. Gallagher; Iftikhar Ahmad; Syed Ali Musstjab Akber Shah Eqani (Environmental Science and Pollution Research, 2014)

Periplasmic nitrate reductase revisited: a sulfur atom completes the sixth coordination of the catalytic molybdenum - Shabir Najmudin; Pablo J. González; José Trincão; Catarina Coelho; Abhik Mukhopadhyay; Nuno M. F. S. A. Cerqueira; Carlos C. Romão; Isabel Moura; José J. G. Moura; Carlos D. Brondino; Maria J. Romão (JBIC Journal of Biological Inorganic Chemistry, 2008)